My hero academia smash!! 4 - Neda, Hirofumi; Cook, Caleb D.; Horikoshi, Kōhei, 1986-; Neda, Hirofumi (San Francisco, CA : VIZ Media, LLC, 2020)
"In this zany volume of the "My Hero Academia" parody series, U.A.'s aspiring heroes move into the dorms to deter bad guys--but the League of Villains somehow enrolls in classes for a day anyway! Then, All Might administers some overly personal life-or-death training, Mineta becomes the subject of a murder mystery, and there's even body swapping! Who knew school could be so much fun?"--Back cover.
"Original concept by Kohei Horikoshi."
Translation of: Boku no hiro akademia sumasshu.
Young Adult
English.
Keywords: Ability -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; High schools -- Comic books, strips, etc. -- Fiction; Humorous stories; Superheroes -- Comic books, strips, etc. -- Fiction; Supervillains -- Comic books, strips, etc. -- Fiction; Ability -- Comic books, strips, etc. -- Fiction; Fantasy graphic novels; High schools -- Comic books, strips, etc. -- Fiction; Humorous graphic novels; Manga; Superhero graphic novels; Superheroes -- Comic books, strips, etc. -- Fiction; Supervillains -- Comic books, strips, etc. -- Fiction; Fantasy comics; Graphic novels; Humorous comics; Superhero comics